Quantification of gas, ash, and sulphate aerosols in volcanic plumes from open path Fourier transform infrared (OP-FTIR) emission measurements at Stromboli volcano, Italy - Smekens, Jean-François; Mather, Tamsin A.; Burton, Mike R.; La Spina, Alessandro; Kabbabe, Khristopher; Esse, Benjamin; Varnam, Matthew; Grainger, Roy G. (Frontiers in Earth Science, 2023)
Field-portable Open Path Fourier Transform Infrared (OP-FTIR) spectrometers can be used to remotely measure the composition of volcanic plumes using absorption spectroscopy, providing invaluable data on total gas emissions. Quantifying the temporal evolution of gas compositions during an eruption helps develop models of volcanic processes and aids in eruption forecasting. Absorption measurements require a viewing geometry which aligns IR source, plume, and instrument, which can be challenging. Here, we present a fast retrieval algorithm to estimate quantities of gas, ash and sulphate aerosols from thermal emission OP-FTIR measurements, and the results from two pilot campaigns on Stromboli volcano in Italy in 2019 and 2021. We validate the method by comparing time series of SO2 slant column densities (SCD) retrieved using our method with those obtained from a conventional UV spectrometer, demonstrating that the two methods generally agree to within a factor of 2. The algorithm correctly identifies ash-rich plumes and gas bursts associated with explosions and quantifies the mass column densities and particle sizes of ash and sulphate aerosols (SA) in the plume. We compare the ash sizes retrieved using our method with the particle size distribution (PSD) of an ash sample collected during the period of measurements in 2019 by flying a Remotely Piloted Aircraft System (RPAS) into the path of a drifting ash plume, and find that both modes of the bimodal PSD (a fine fraction with diameter around 5-10 m and a coarse fraction around 65 m) are identified within our datasets at different times. We measure a decrease in the retrieved ash particle size with distance downwind, consistent with settling of larger particles, which we also observed visually. We measure a decrease in the SO2/SA ratio as the plume travels downwind, coupled with an increase in measured SA particle size (range 2-6 m), suggesting rapid hygroscopic particle growth and/or SO2 oxidation. We propose that infrared emission spectroscopy can be used to examine physical and chemical changes during plume transport and opens the possibility of remote night-time monitoring of volcanic plume emissions. These ground-based analyses may also aid the refinement of satellite-based aerosol retrievals.